Export Barriers Faced by Pakistani and Irani Small and Medium Sized Manufacturing Companies - Mutahhar Ali; Ali Reza Habibi (Dialogue Social Science Review (DSSR), 2025)
The global economy relies heavily on SMEs. They foster innovation, create jobs, and advance the economy for everyone. This study compared export issues faced by Pakistani and Iranian manufacturing SMEs. To understand export restrictions, the research uses mixed methods, including qualitative and quantitative methods. It starts with qualitative literature and policy document studies to identify and categorize impediments. It then ranks sectors by exposure and prioritizes barriers using quantitative methods like AHP and TOPSIS. This study includes a diverse and competent set of stakeholders participating in Pakistani SMEs' export activity. Analysis found that market challenges like collecting marketing information, logistical issues, and environmental limits are important impediments in both countries. Pakistani SMEs consider technological and procedural challenges as separate, while Iranian SMEs see technology issues as regulatory and environmental issues. Results demonstrate that SMEs in both countries have many issues, but how they interact and effect each other is different, therefore policies must be customized to each case. Future research could include more countries from similar developing regions to evaluate SME obstacles and find common themes or unique contextual distinctions. Keywords: Export Barrier, Pakistani SME, Irani SME, Economy Etc. https://doi.org/10.5281/zenodo.16731376